PENGARUH DOSIS STATIN TERHADAP KADAR LIPID PLASMA DAN OUTCOME FUNGSIONAL PADA PASIEN STROKE ISKEMIK - Franz Julius H*, Yuneldi Anwar*, Darulkutni Nasution* (NEURONA, 2011)
INTRODUCTION HIGH LEVEL OF CHOLESTEROL IS THE RISK FACTOR FOR ISCHEMIC STROKE EARLY TREATMENT WITH STATINS MAY REDUCE PLASMA LIPID LEVEL AND THEREFORE IMPROVE OUTCOMES OF ACUTE ISCHEMIC STROKE